Alcune riflessioni sul significato gnoseologico della metapsicologia freudiana - Baldini, Franco (Metapsychologica - rivista di psicanalisi freudiana, 2024)
Some reflections on the gnoseological significance of freudian metapsychology. The article examines Freud’s metapsychology, highlighting its central role in understanding the human mind while critiquing contemporary misunderstandings that have led to its gradual rejection within the scientific community and the psychoanalytic movement. It also challenges the widespread notion that cognitive syntax can directly correlate with neurophysiological dynamics, arguing that thought cannot be reduced to mere neuronal processes. The article further contends that Freudian metapsychology can serve as a conceptual bridge between neurophysiology and cognition, focusing on the concept of drive. It demonstrates that metapsychology, far from being obsolete, remains an indispensable interpretative tool for investigating the human psyche, provided it is developed and properly reevaluated in light of current knowledge.